Control of heat supply of building based on the use of individual heat point of original design - Лисенко, Оксана Миколаївна; Кужель, Лілія Миколаївна; Божко, Ігор Костянтинович (Eastern-European Journal of Enterprise Technologies, 2015)
The literature states that the transition from central heat points to individual heat points with the installation of appropriate automation allows to achieve a heat energy saving of more than 20%, but reliable experimental data, substantiating this position are not found today. Therefore, long-term experimental studies of heat supply of administrative building based on the individual heat point of original design to determine the real heat energy saving in actual practice taking into account environmental factors were conducted. Based on the experimental data, graphical dependencies of consumption of the heat carrier, heat energy and heat carrier temperature on the ambient temperature for two operation modes of the individual heat point with the calculated heat energy saving were constructed. The effectiveness of introducing the individual heat point was also determined. As a result of experimental studies, it was found that the higher the ambient temperature, the more unreasonable heat energy consumption with centralized unregulated heat supply, especially at the beginning and end of the heating season. Therefore, introducing individual heat points is one way to increase energy efficiency during new construction and modernization of existing buildings, which enhances the heat supply quality and efficiency thus providing consumers with comfort. Long-term experimental studies of heat supply of administrative building based on the individual heat point have shown the possibility of heat energy saving of up to 15%. The experimental data are important for providing recommendations on mass introduction of individual heat points of different capacities for housing and communal services.